Olfactory dysfunction is worse in primary ciliary dyskinesia compared with other causes of chronic sinusitis in children. Issue 10 (28th February 2018) - Pifferi, Massimo; Bush, Andrew; Rizzo, Michele; Tonacci, Alessandro; Di Cicco, Maria; Piras, Martina; Maggi, Fabrizio; Paiola, Giulia; Michelucci, Angela; Cangiotti, Angela; Peroni, Diego; Caramella, Davide; et al.
Abstract : Cilia have multiple functions including olfaction. We hypothesised that olfactory function could be impaired in primary ciliary dyskinesia (PCD). Olfaction, nasal nitric oxide (nNO) and sinus CT were assessed in patients with PCD and non-PCD sinus disease, and healthy controls (no CT scan). PCD and non-PCD patients had similar severity of sinus disease. Despite this, defective olfaction was more common in patients with PCD (P<0.0001) and more severe in patients with PCD with major Transmission Electron Microscopy (TEM) abnormalities. Only in classical PCD did olfaction inversely correlate with sinusitis and nNO. We speculate that defective olfaction in PCD is primary in nature.